Test on Emerita analoga as Cholesterol Reducing Agent on Mus musculus BALB/C - D. Kardaya; T. N. Ralahalu; . Zubir; M. Purba; A. Parakkasi (Jurnal Ilmu dan Teknologi Peternakan, 2011)
A reasonable effort to reduce cholesterol content of meat could be done by ration manipulation. Sea animals are known having high free fatty acid of omega 3 and 6 series. These nutrients could reduce meat cholesterol level if included in ration. The study aimed to reveal the effect of various level of sand crab (Emerita analoga) powder supplemented in ration on performances and meat cholesterol level of Mus musculus balb/c mouse. Thirty two mice, consisted of 16 male and 16 female of a 28-day old, were fed on one of four different rations with four replications in a factorial arrangement according to completely randomized design. The rations contained isoprotein and isoenergy but with different level of sand crab powder, i.e. 0, 12.5, 25, and 37.5% of the ration dry matter. The mice were treated for five weeks and each week body weight or orts was measured.  At the end of experimental period, the mice were slaughtered and carcassed and each of the right leg was sampled for meat cholesterol analysis. The data collected were analyzed with analyzes of variance and Duncan’s multiple range test was applied to separate the different means of each treatment. In addition, a polynomial orthogonal regression was applied to predict optimal level of sand crab supplementation. Result of the study revealed that experimental ration affected (P<0.05) feed consumption, weight gain, feed conversion, and meat cholesterol level. Moreover, feed consumption, weight gain, and feed conversion were affected (P<0.01) by sex of the mouse. Meanwhile, meat cholesterol level was not affected by sex. The experimental rations containing 25% of sand crab powder resulted in the best performances of the mouse and the optimal level predicted from polynomial graph was 23.02%.